(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Uzbekistan faces significant geoecological challenges that have widespread consequences for both the country and the broader Central Asian region. The rapid expansion of industrial activities, intensive agriculture, deforestation, and water resource mismanagement have led to severe environmental degradation. The Aral Sea crisis remains one of the most striking examples of ecological catastrophe, significantly impacting climate, biodiversity, and public health. Desertification, soil erosion, air pollution, and water contamination continue to pose serious threats to sustainable development. This paper explores the key geoecological problems in Uzbekistan, their causes, and their consequences for the region. The study further discusses possible mitigation strategies and policy recommendations for improving environmental sustainability in the country.